Optimalisasi Literasi Wakaf Produktif dalam Pemberdayaan Usaha Mikro Kecil dan Menengah Muslim untuk Mewujudkan Kemandirian Ekonomi Berkelanjutan - Sujatna, Yayat; Saputro, Ahmad Eko; Achmad, Nur (Forum Kerjasama Pendidikan Tinggi, 2026)
Muslim Micro, Small, and Medium Enterprises play a strategic role in promoting local economic empowerment and enhancing community welfare. However, in practice, many business actors still face limited access to capital that complies with Islamic principles as well as a low level of understanding of Islamic financial instruments, including productive waqf. CV. Sarana Teknik Industri, as the program partner, possesses strong social and economic potential through a socially oriented business model, yet has not optimally utilized its assets and resources to support sustainable business development. This community service program aims to strengthen productive waqf literacy among MSME employees in order to promote economic independence based on Islamic values. The methods employed include productive waqf literacy training, mentoring in Islamic financial management, and the design of productive asset management models. Program evaluation was conducted through pre-test and post-test assessments involving 13 employees, complemented by qualitative observations of changes in participants’ attitudes and social initiatives. The results indicate a 33% increase in participants’ understanding, from an average pre-test score of 52% to 85% in the post-test. Furthermore, participants demonstrated a mindset transformation, as reflected in the emergence of internal initiatives such as the establishment of an employee-based productive waqf program. This program demonstrates that productive waqf literacy not only enhances knowledge but also fosters economic independence, social innovation, and business sustainability among MSMEs. These findings provide a basis for recommending that other Muslim MSMEs integrate productive waqf as a sustainable instrument for economic empowerment.